Bile Acid-Mediated Control of Liver Triglycerides - Fuchs, Claudia; Claudel, Thierry; Trauner, Michael (Seminars in Liver Disease, 2013)
Bile acids (BAs) are steroidal molecules generated in the liver by cholesterol oxidation. Beside their well-established role in lipid absorption and cholesterol homeostasis, they function as signaling molecules and activate dedicated BA receptors such as the farnesoid X receptor (FXR) and the G-protein coupled receptor TGR5. Through activation of downstream signaling pathways of these key receptors, BAs regulate not only their own synthesis and enterohepatic circulation, but also impact on hepatic lipid, glucose, and energy homeostasis. Therefore, BA-regulated signaling pathways have emerged as attractive targets for understanding the regulation of hepatic triglyceride metabolism in health and disease and treating fatty liver disease and associated metabolic disorders.
Keywords: farnesoid X receptor; TGR5; FGF15/19/21; nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; glucose